Association of Albumin to Creatinine Ratio with Severity of Coronary Artery Disease (University Heart Journal, 2015)
Coronary artery disease (CAD) is the most common cause of mortality and morbidity all over the world. It is also becoming a significant burden on healthcare service in Bangladesh. Atherosclerosis is the main pathology behind coronary artery disease. Endothelial dysfunction plays a crucial role in the process of atherosclerosis. Microalbuminuria (MA) is a reliable marker of endothelial dysfunction. This is why microalbuminuria is recognized as a simple marker of atherogenic milieu It was a cross sectional analytical study carried out in the department of Cardiology, Dhaka Medical College Hospital, Dhaka during the period of May, 2013 to April, 2014. After ethical consideration a total of 120 patients with IHD admitted in the department of Cardiology who fulfilled the inclusion and exclusion criteria and underwent coronary angiogram were taken as sampling population by purposive sampling. 1st morning spot urine sample was taken for measurement of ACR.Microalbumnuria was measured by rate nephelometry using Behring protein analyzer. All the study subjects were placed into two groups according to ACR value (group I- positive urinary ACR >30 mg/g & group II-Normal urinary ACR